Effectiveness of Illness Management and Recovery program on people with severe mental illnesses: a systematic review and meta-analysis - Goh, Yong Shian Shawn; Ow Yong, Jenna Qing Yun; Li, Amy Ziqiang (Frontiers in Psychiatry, 2023)
Background The Illness Management and Recovery (IMR) program has been established in response to the challenges faced by people with severe mental illnesses (SMIs). The program emphasizes the self-management of mental health conditions and the achievement of personally meaningful goals. However, reviews on its efficacy remain scarce, especially in recent years. Objective This review aimed to examine the efficacy of IMR in improving personal-recovery outcomes among people with SMIs. Methods A search was conducted on seven databases (CINAHL, Embase, ProQuest, PsycINFO, PubMed, Scopus, and Web of Science) from inception to February 2022, without limits on the dates and types of publications. Studies were included if they had examined the efficacy of IMR in one or more outcomes, investigated at least one group of participants, and been published in English. The participants were adults (at least 16 years of age) with a formal diagnosis of at least one SMI. Results Fourteen studies were included in this review, and eight outcomes were examined: personal recovery, global functioning, social functioning, hope, perceived social support, quality of life, substance abuse, and knowledge of mental illness. There is limited evidence on the superiority of IMR to existing treatment plans or other interventions in improving the outcomes of interest among people with SMIs. However, the low attendance rates in many included studies suggest the presence of a threshold of exposure to IMR beyond which its treatment effects could be observed. Suggestions for future IMR implementation are discussed. Conclusions The IMR program may serve as an alternative or complementary intervention for people with SMIs, especially with enhanced program exposure and access to resource materials. Systematic review registration https://inplasy.com/inplasy-2022-10-0005/.